2012
DOI: 10.1089/bsp.2012.0041
|View full text |Cite
|
Sign up to set email alerts
|

Public Response to an Anthrax Attack: A Multiethnic Perspective

Abstract: The 2001 anthrax attacks emphasized the need to develop outreach that would more effectively support racial/ethnic minority populations during a bioterrorism incident. Given the importance of antibiotic prophylaxis in a future anthrax attack, it should be a priority to better support racial/ ethnic minorities in mass dispensing programs. To examine the needs and perspectives of racial/ ethnic minorities, this study used a nationally representative poll of 1,852 adults, including 1,240 whites, 261 African Ameri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…In the past decade, some terrorists used the anthrax agents and/or their associated toxins as bioweapons. In addition, some people have been exposed to anthrax spores during bioterrorism events [3, 4]. These make it necessary to study anthrax pathogenesis, treatment, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, some terrorists used the anthrax agents and/or their associated toxins as bioweapons. In addition, some people have been exposed to anthrax spores during bioterrorism events [3, 4]. These make it necessary to study anthrax pathogenesis, treatment, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In telephone surveys asking respondents what prophylactic treatment they would seek in the event of a mass anthrax contamination, less willingness to comply with safety recommendations was evident among participants from minority groups which had lower initial levels of trust in government. In other studies, African‐American respondents reported lower levels of confidence in anthrax vaccination programs, a finding described as related to the legacy of the Tuskegee experiments in which black subjects were intentionally exposed to syphilis without consent (SteelFisher et al : 402‐403). In this instance, cultural context contributes to the pre‐existing schema through which government policies and actions are analyzed by different segments of the public (Axelrod : 1248‐1266).…”
Section: Biological Attacks and Public Trustmentioning
confidence: 96%
“…Some of the most comparable examples include Iyengar and Kinder, 1987; Merolla and Zechmeister, 2009; Raber, Hibbard, and Greenwald, ; and SteelFisher et al., .…”
mentioning
confidence: 99%
“…This analysis resulted in 10 perception variables and 2 action-related variables. The perception variables were named: (1) trust authority information, (2) trust authority response, (3) confidence in knowledge of ''dirty bomb,'' (4) need to know who is responsible, (5) distrust in authority, (6) family and pet concerns, (7) radiation concerns, (8) anti-compliant behavior, (9) believe I am prepared, and (10) know what to do. The 2 action variables were: (1) I would stay inside and (2) I have an emergency plan.…”
Section: Data Reduction and Cluster Analysismentioning
confidence: 99%
“…7 Key to this is the establishment of effective communication messages to reduce feelings of fear, distress, helplessness, and confusion. 8,9 Although post hoc analyses of terrorist emergencies in the United States, such as September 11, the Boston Marathon bombing, and the San Bernardino shootings, suggest that the public is generally willing to comply with government instructions, 10 studies also suggest that significant barriers may exist. 11,12 These barriers include distrust, lack of confidence, and fear of discrimination by the government or public health systems, [12][13][14] as well as concerns about information messaging credibility, inaccuracy, ambiguity, and inconsistency.…”
mentioning
confidence: 99%